2013
DOI: 10.1177/0022034513499350
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of ATG5 Shows a Role of Autophagy in Salivary Homeostatic Control

Abstract: Autophagy is a catabolic pathway utilized to maintain a balance among the synthesis, degradation, and recycling of cellular components, thereby playing a role in cell growth, development, and homeostasis. Previous studies revealed that a conditional knockout of essential member(s) of autophagy in a variety of tissues causes changes in structure and function of these tissues. Acinar cell-specific expression of knocked-in Cre recombinase through control of aquaporin 5 (Aqp5) promoter/enhancer (Aqp5-Cre) allows u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 26 publications
0
44
0
1
Order By: Relevance
“…Further work is necessary to determine the existence of potential other immunological drivers. Background: Labial salivary glands (LSG) of Sjögren's syndrome (SS) patients show alterations indicative of endoplasmic reticulum (ER) stress, such as ER cistern dilatation (1) and mucin accumulation (2). Pro-inflammatory cytokines induce ER stress, but it is not well known if the ER stress is an initial event in the onset of a chronic disease or if is secondary to the inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work is necessary to determine the existence of potential other immunological drivers. Background: Labial salivary glands (LSG) of Sjögren's syndrome (SS) patients show alterations indicative of endoplasmic reticulum (ER) stress, such as ER cistern dilatation (1) and mucin accumulation (2). Pro-inflammatory cytokines induce ER stress, but it is not well known if the ER stress is an initial event in the onset of a chronic disease or if is secondary to the inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Primary Sjogren's syndrome (pSS) is a systemic autoimmune disease characterized by infiltration of exocrine glands by T and B cells that, producing chemokines and cytokines, coordinate the chronic inflammatory process. No data on the role of autophagy in pSS are available in humans, although studies in mice demonstrated its involvement in the salivary and lacrimal gland homeostasis (2,3). Objectives: We investigated the autophagy process in salivary gland tissue and in peripheral T lymphocytes from pSS patients to evaluate its possible implication in the pathogenesis of the disease.…”
mentioning
confidence: 99%
“…In these mice, Cre recombinase is specifically expressed in salivary acinar cells via the use of the Aquaporin 5 (Aqp5) promoter, which is the principle aquaporin water channel protein expressed on the apical surface of salivary acinar cells23. Salivary glands have relatively low baseline levels of autophagy24 and correspondingly Atg5 f/f ;Aqp5-Cre mice display no differences in baseline levels of apoptosis, proliferation, or salivary flow rates22. The purpose of this study was to determine the role of autophagy in the response of the salivary glands to targeted head and neck radiation and to better define the relationship between autophagy and apoptosis in salivary glands following radiation by evaluating the binding of Ambra-1 to Bcl-2 or Beclin-1.…”
mentioning
confidence: 99%
“…Aquaporin 5 (AQP5) is the primary aquaporin channel expressed on acinar cells and is localized to the apical membrane of acinar cells but not ductal cells. In these mice, the Cre recombinase is knocked-in to exon 1 of 1 copy of endogenous AQP5, and the Atg5 gene is flanked with lox P sites, leading to the preferential loss of Atg5 in salivary acinar cells, thereby rendering these mice autophagy deficient (Morgan-Bathke et al 2013). Initial characterization of this mouse model focused on homeostasis parameters in young mice (4-6 wk) and found that the Atg5 f/f ;Aqp5-Cre mice have no differences in apoptosis, proliferation, or carbachol-induced salivary secretion.…”
Section: Autophagy and Homeostasis Of Normal Salivary Glandsmentioning
confidence: 99%